Impact of Dollar Fluctuation on Gold and Crude Oil Prices - Joshi, Divyang J. (Indian Journal of Finance, 2011)
The ₹/$ rate is very important for the movement of prices of Gold and Crude oil. The ₹/$ rate is considered as a base by the commodity traders to forecast the Gold or Crude oil movement. This gives a strong subjective background to test the existence of any such relationship in India. This paper focuses on to establish and validate the long term relationship of commodities' prices (Gold&Crude Oil) with Exchange rate (₹/Dollar.) in the Indian context. There are numerous traders in India who trade in commodities on the basis of relationship of ₹/$ exchange rate and Commodity price. There are many other factors on which the prices of Gold and crude oil may depend. They are government policies; budget, inflation, economic and political condition of the country etc. affect the prices of Gold and Crude oil. But this study focuses only on one independent variable i.e. ₹/$ exchange rate. The data of ₹/$ weekly closing rate taken as an independent variable and the prices of Gold and Crude oil are taken as dependent variables. The correlation-regression analysis and ADF test is used to find out relationship among ₹/$ exchange rate volatility v/s Gold & Crude oil. The ₹/$ exchange rate found stationary with the help of ADF test. The study shows the negative relationship between ₹/$ exchange rate and Gold and Crude oil.